Stereoselective synthesis of trans-3-functionalized-4-pyrazolo[5, 1-b]thiazole-3-carboxylate substituted β-lactams: Potential synthons for diverse biologically active agents. Issue 19 (1st October 2020) - Berry, Shiwani; Bari, Shamsher S.; Yadav, Pooja; Garg, Ankita; Khullar, Sadhika; Mandal, Sanjay K.; Bhalla, Aman
Abstract: An efficient protocol for the stereoselective synthesis of pyrazolo[5, 1- b ]thiazole-3-carboxylate tethered β-lactam conjugates 8a–j from novel pyrazolo [5, 1- b ]thiazole-3-carboxylate substituted Schiff's bases 6a–f is reported here. The reaction between various ketene precursors and novel Schiff's bases 6a–f afforded exclusive formation of trans -β-lactams 8a–j . The substrate scope of this approach was investigated extensively by varying different groups (R, Z). All the novel compounds were characterized using various spectroscopic techniques, such as FT-IR, 1 H NMR, 13 C NMR, elemental analysis, 13 C NMR (DEPT-135), and mass spectrometry in representative cases. Single crystal X-ray crystallographic study of trans -ethyl 7-(1-(4-methoxyphenyl)-4-oxo-3-phenoxyazetidin-2-yl)-6-methyl-2-(methylthio)pyrazolo[5, 1- b ]thiazole-3-carboxylate 8a has confirmed the molecular structure and the stereochemical outcome. To the best of our knowledge, the synthesis of such types of Schiff's bases and β-lactam conjugates has not been reported so far. Graphical Abstract: